Tacrolimus Ointment for Treatment of Vernal Keratoconjunctivitis - Al-Amri, Abdulrahman M. (Middle East Afr J Ophthalmol, 2016)
PURPOSE: To evaluate the safety and efficacy of tacrolimus 0.1% ointment for the treatment of refractory vernal keratoconjunctivitis (VKC). MATERIALS AND METHODS: This prospective, nonrandomized case series enrolled 20 patients (40 eyes) with severe VKC, who were treated with tacrolimus 0.1% ointment. The mean age of the patients was 18.25 ± 4.2 years (range, 9–31 years). Each patient completed a follow-up period of at least 24 months. The main outcome measure was the clinical response to treatment. RESULTS: Significant improvements in clinical signs and symptoms were achieved in all patients 6 weeks after starting treatment with topical tacrolimus. Treatment was gradually reduced, with increasing intervals between applications. VKC recurred in all patients who attempted to discontinue treatment. No additional medications were required and no significant changes in visual acuity or refraction were documented. Five patients discontinued treatment due to a severe burning sensation and were excluded from the study. CONCLUSIONS: Tacrolimus, 0.1% ointment, is a safe and effective treatment for VKC refractory to standard treatment and may be used as a substitute for steroid treatments used to controlled disease activity. However, adverse effects could cause poor patient compliance.